If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6k + 2) = -5k + -7 Reorder the terms: -1(2 + 6k) = -5k + -7 (2 * -1 + 6k * -1) = -5k + -7 (-2 + -6k) = -5k + -7 Reorder the terms: -2 + -6k = -7 + -5k Solving -2 + -6k = -7 + -5k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '5k' to each side of the equation. -2 + -6k + 5k = -7 + -5k + 5k Combine like terms: -6k + 5k = -1k -2 + -1k = -7 + -5k + 5k Combine like terms: -5k + 5k = 0 -2 + -1k = -7 + 0 -2 + -1k = -7 Add '2' to each side of the equation. -2 + 2 + -1k = -7 + 2 Combine like terms: -2 + 2 = 0 0 + -1k = -7 + 2 -1k = -7 + 2 Combine like terms: -7 + 2 = -5 -1k = -5 Divide each side by '-1'. k = 5 Simplifying k = 5
| -5b+2=52 | | 0.50x+0.25(70)=22.5 | | 2x+27=2x-11+100 | | 21+7z-21=6z+1 | | 5(4x-3)+7=-1 | | 2x(3x+1x)=24 | | -4+5v=-14 | | -2a+2+3a=7-26 | | 1.5x^2-4x-3.5=0 | | -4+5v= | | -67=20+p | | 8(4-6)=7x+2 | | 10+2n=-7 | | (3a-b)(a^2-b^3)-a^2(a+2b)+(3a+b)(3a-b)=0 | | x+(x+3)=28 | | 12x^2+7x= | | -42m-11=109 | | C-36=-18 | | 2(x+4)=72 | | -2u-14=8u+16 | | 5-3(x-7)=8 | | 24=8xblank | | 10x-24=10 | | f(x)=45-15x | | x+123=4 | | 0.6(x+6)+1.6(x-5)= | | 3(2m-1)=-9x | | 5(2x+6)=-3x-5+8x | | 6-3(-8r-7)=3r+6 | | (x-2)x+(2x-3)3x= | | x^2-5x-34=2 | | q/24 |